Raccoon Roundworm (Baylisascaris procyonis): Are You at Risk? - Brown, Michelle H. (Wildlife Rehabilitation Bulletin, 2007)
Zoo veterinary technicians, wildlife rehabilitators, parents, and pediatricians are becoming increasingly concerned about the raccoon roundworm, Baylisascaris procyonis, due to the recent rise in the number of human cases of neural larva migrans. The worm is classified under Phylum Nemathelminthes, Class Nematoda, member of the Family Ascaridae, and Superfamily Ascaridoidea, which represents intestinal worms with direct life cycles. This roundworm is common in raccoons throughout the US where prevalence in some populations has grown to greater than 80 per- cent. B. procyonis may exhibit no clinical or pathological signs in raccoons where the larvae develop to adult worms in the small bowel. However, when aberrant hosts become infected with B. procyonis, the larvae migrate throughout the liver, brain, spinal cord, and other organs causing severe central nervous system disorders and other tissue damage which eventually results in death. Parasitic infection is difficult to detect in aberrant hosts. Even if infection with B. procyonis is suspected, there is no proven effective therapy or existing vaccine. There are two main categories of humans that are at risk for this disease: those who accidentally come in contact with rac- coon feces in their neighborhoods and those who work directly with rac- coons. Fortunately, preventive measures including discouraging raccoons’ visitation near homes by removing food and shelter sources and implemen- tation of proper cleaning methods for raccoon enclosures can decrease risk to these groups.